Intention to purchase Islamic life insurance policy: evaluation of the mediating effects of perceived trust - Aziz, Shahab; Md Husin, Maizaitulaidawati; Haron, Razali; Afaq, Zahra (2019)
This paper aims to investigate the factors affecting individuals’ intention to purchase Islamic life insurance policy in Pakistan. The decomposed theory of planned behaviour was adapted and further extended, and the mediating effects of perceived trust were incorporated into the framework. A total of 449 questionnaires were collected using judgemental sampling technique and analysed using SmartPLS. Of all the hypotheses, one was rejected. Attitude and subjective norm were found to have a positive relationship with intention. Perceived religiosity and knowledge have a positive relationship with attitude, media referent and word of mouth have a positive relationship with subjective norm, and financial self-efficacy and resource facilitating conditions have a positive relationship with perceived behavioural control. In addition, trust was found to have a mediating effect on religiosity and attitude. However, perceived behavioural control was found to have an insignificant relationship with intention. The contribution and implications of the study are further discussed.